Protein kinase C θ cooperates with Vav1 to induce JNK sctivity in T-cells - Möller, Andreas; Dröge, Wulf (The journal of biological chemistry, 2001)
Here we show that in human T-cell leukemia cells Vav1 and protein kinase C θ (PKCθ) synergize for the activation of c-Jun N-terminal kinase (JNK) but not p38 MAP kinase. Vav1 and PKCθ also cooperated to induce transcription of reporter genes controlled either by AP-1 binding sites or the CD28RE/AP composite element contained in the IL-2 promoter by stimulating the binding of transcription factors to these two elements. Dominant negative versions of Vav1 and PKCθ inhibited CD3/CD28-induced activation of JNK, revealing their relative importance for this activation pathway. Gel filtration experiments revealed the existence of constitutively associated Vav1/PKCθ heterodimers in extracts from unstimulated T-cells, whereas T-cell costimulation induced the recruitment of Vav1 into high molecular weight complexes. Several experimental approaches showed that Vav1 is located upstream from PKCθ in the control of the pathway leading to synergistic JNK activation. Vav1-derived signals lead to the activation of JNK by at least two different pathways. The major contribution of Vav1 for the activation of JNK relies on the PKCθ-mediated Ca2+-independent synergistic activation pathway, whereas JNK is also activated by a separate Ca2+-dependent signaling route.